2017
DOI: 10.1186/s11671-017-2102-0
|View full text |Cite
|
Sign up to set email alerts
|

Semiconductor Gas Sensors Based on Pd/SnO2 Nanomaterials for Methane Detection in Air

Abstract: Semiconductor sensors based on nanosized Pd-containing tin dioxide have been obtained by a sol–gel technique. Semiconductor gas-sensitive materials were characterized by transmission electron microscopy (TEM) and X-ray diffraction (XRD) methods. Influence of Pd additives on sensitivity of the sensors to methane has been studied. Temperature dependences of electrical resistance in air and sensor response to methane on palladium content for the sensors based on nanosized materials Pd/SnO2 have been investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 32 publications
(37 reference statements)
1
34
0
Order By: Relevance
“…It was observed that the initial resistances of Pd:SnO 2 was much higher than pure SnO 2 and Ni:SnO 2 nanorods sensors. A similar result was also observed by Chen et al and Fedorenko et al 28,29 It was explained that the presence of two forms of Pd clusters (Pd and PdO) in the SnO 2 sensor system influenced the initial resistance. This is because more chemisorption of oxygen takes place at the common edge between Pd/PdO and SnO 2 , which eventually increased the initial resistance of the sensor.…”
Section: Gas Sensing Measurementsupporting
confidence: 85%
“…It was observed that the initial resistances of Pd:SnO 2 was much higher than pure SnO 2 and Ni:SnO 2 nanorods sensors. A similar result was also observed by Chen et al and Fedorenko et al 28,29 It was explained that the presence of two forms of Pd clusters (Pd and PdO) in the SnO 2 sensor system influenced the initial resistance. This is because more chemisorption of oxygen takes place at the common edge between Pd/PdO and SnO 2 , which eventually increased the initial resistance of the sensor.…”
Section: Gas Sensing Measurementsupporting
confidence: 85%
“…According to the XRD study, only cassiterite phase was present in the gassensitive material ( Figure 2). e XRD sizes of SnO 2 particles are 13.9 and 12.6 nm for the undoped and doped with 0.24 wt.% Pd materials, respectively, that could be explained by a stabilization role of the palladium additives [26].…”
Section: Resultsmentioning
confidence: 97%
“…The sensors using Pd-doped TiO 2 fibers exhibited encouraging gas sensing characteristics like low operation temperature and adequate gas response [ 56 ]. The sensor response to methane was found to be higher and fast-acting, when 1.41% palladium was added to tin dioxide, compared to the non-doped tin oxide [ 57 ]. These gases are seen to be sensed by palladium-doped SnO 2 , but at concentrations more than 0.5% palladium [ 29 ], which pave chances that only CO gas gets sensed at this lesser concentration of 0.1–0.2% Pd, making this sensor highly selective for CO gas, in that case.…”
Section: Resultsmentioning
confidence: 99%